A systematic review of eHealth technologies for breast cancer supportive care. (March 2023) - Gyawali, Bishal; Bowman, Meghan; Sharpe, Isobel; Jalink, Matthew; Srivastava, Siddhartha; Wijeratne, Don Thiwanka
Highlights: Patients with breast cancer are broadly satisfied with eHealth interventions. eHealth interventions have mixed effects on patient symptoms and quality of life. The literature on eHealth for breast cancer supportive care is highly heterogeneous. Abstract: Breast cancer places a substantial burden on patient physical and mental wellbeing, and the delivery of high-quality supportive care is essential at all stages of the disease. Given the increased uptake of technology in recent years, eHealth interventions may be a convenient and accessible method for supportive care. Within this context, we conducted a systematic review to describe and quantify the use of eHealth for breast cancer supportive care. We searched MEDLINE, EMBASE, and CINAHL databases for primary research studies published from 2016 to 2021 (present) that assessed the effects of eHealth interventions on adult patients with breast cancer. We explored the effects of the interventions on patient symptoms, lifestyle, satisfaction, and barriers, as well as factors related to feasibility and implementation. The risk of bias of each study was also assessed. Findings were presented according to stage of cancer care. We identified 43 relevant studies capturing n = 6, 285 patients (30 randomized controlled trials and 13 non-randomized interventional studies); 5 evaluated patients who were newly diagnosed, 16 evaluated patients undergoing active treatment, and 22 evaluated patients in post-treatment follow-up. A total of 19 studies used mobile apps, 18 used online patient portals, 5 used text messaging, and 1 used both a patient portal and text messaging. We found that patients were broadly satisfied with the eHealth interventions; however, findings were less consistent for symptom and lifestyle-related outcomes. Eight studies were judged as high risk of bias. There was substantial between-study heterogeneity, which made it challenging to discern consistent trends. Overall, future research should continue to explore the use of eHealth for breast cancer supportive care, with a focus on improving patient symptoms.